Pelabelan Super Graceful pada Graf B dan Graf serta Implementasinya pada Matlab - Pertiwi, Ruvita Iffahtur (Jurnal Likhitaprajna, 2024)
Suppose G is a graph with vertices p dan edges q. Super graceful labeling is a one-to-one function maping on f:V(G) È E(G)  {1,2, … , p + q} such that f(uv) = ½f(u) – f(v)½ differs for each edge uv Î E(G). A graph G is called super graceful if it can be labeled according to the definition of super graceful labeling. The graph B(m,n,k) is a graph consisteing of a path graph of length k conneting the star graph K(1,m) and K(1,n) at the pendant ends. Meanwhile, the graph Pn(1,2,…,n) is a path graph of length by n combining each vertex on the path graph with edges i to i members (1,2,…,n). In this journal, it will be shown that graph B(m,n,k) and graph Pn(1,2,…,n) are super graceful graphs.